UJI BAKTERIOLOGIS PADA MATA AIR DI JORONG BATU KARAK KANAGARIAN DILAM KABUPATEN SOLOK - Amelya, Siska; Indriati, Gustina; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Community in Batu Karak kanagarian of Dilam case sub-province of Solok use spring water as potable drinking water well directly or paraphrased in advance. In Batu Karak kanagarian of Dilam case sub-province of Solok there are five springs where the water fountain is popularly but used as a drinking water fountain that is only two spring, Â Cibuak Gadang and Cibuak Karang . Cibuak Gadang located on the edge of fields and Cibuak Karang located on the edge of the river. Viewed in terms of the availability of possible locations for the second pollution this spring. Based on information obtained from clinic staff Batu Karak kanagarian of Dilam that disease most often suffered diarrhea and suspected people are this could be due to diarrheal diseases due to microbial infection through drinking water . The study was conducted to determine the density of Escherichia coli at water points in Batu Karak kanagarian of Dilam case sub-province of Solok.The study was carried out in July - August 2013 with a two-point sampling of the water in Batu Karak kanagarian of Dilam case sub-province of Solok regency and extended the analysis of the Labor mikrobiologis Biology STKIP PGRI West Sumatra. This research using the MPN method 3:3:3 modes with10ml of treatment,1ml and 0.1ml. The results showed that the density of E. coli at water points Cibuak Gadang is 1100/100 ml and E. coli densities in Cibuak Karang is â¥ 2400/100 ml . From the results of this study note that the water from these springs is not eligible to be consumed as drinking water and do not meet water quality requirements set by the government .Â